Agriculture - Interests and challenges in the WTO - Silva, Dutra, Ligia (2017)
Ligia Dutra Silva IFPRI POLICY SEMINAR Global food security and the WTO: The role of Mercosur countries FEB 22, 2017 - 12:15 PM TO 01:45 PM EST